OPTIMIZING USER INTERFACE DESIGN LANDING PAGE WITH HCD (HUMAN CENTERED DESIGN) A CASE STUDY OF MELANGKAH ADS - Nasution, Rojesh Mangaraja Soalohon; Adriyanto, Andreas Rio (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Digitalization brings development to companies, which involves media to disseminate information in the form of services provided by companies, the media can be through digital media such as landing pages. Melangkah Ads is a company engaged in digital marketing and already has a landing page, but there is a problem according to users, around 30 respondents in 60% said that the landing page used is difficult to get information about products and services, as well as the USP provided (Maulana, 2024). So that the author optimizes the landing page by using human centered design with various stages of inspiration, ideate, and implementation to get problems, and provide solutions. The author also conducted an interview with the Maulana as a product designer to get various problems that occurred. After getting the problem, the author conducts an analysis that ultimately results in design of landing page interface design, so that the latest landing page design is able to convey information about USP fiber products and services that the company wants.